2014
DOI: 10.1038/srep07389
|View full text |Cite
|
Sign up to set email alerts
|

Electron tomography provides a direct link between the Payne effect and the inter-particle spacing of rubber composites

Abstract: Rubber-filler composites are a key component in the manufacture of tyres. The filler provides mechanical reinforcement and additional wear resistance to the rubber, but it in turn introduces non-linear mechanical behaviour to the material which most likely arises from interactions between the filler particles, mediated by the rubber matrix. While various studies have been made on the bulk mechanical properties and of the filler network structure (both imaging and by simulations), there presently does not exist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 35 publications
2
20
1
Order By: Relevance
“…In the previous works, various heterogeneous structures have been observed by FIB-SEM and electron tomography: that is, island-sea, cylinder, gyroid and lamellar structures for block and graft copolymers [1,2] as well as dispersion of primary nanoparticles, structure of secondary aggregates, and 3D filler-network structure for filled polymers [1,2,[6][7][8]. Some important findings were achieved by 3D observations through FIB-SEM and electron tomography.…”
Section: Introductionmentioning
confidence: 92%
“…In the previous works, various heterogeneous structures have been observed by FIB-SEM and electron tomography: that is, island-sea, cylinder, gyroid and lamellar structures for block and graft copolymers [1,2] as well as dispersion of primary nanoparticles, structure of secondary aggregates, and 3D filler-network structure for filled polymers [1,2,[6][7][8]. Some important findings were achieved by 3D observations through FIB-SEM and electron tomography.…”
Section: Introductionmentioning
confidence: 92%
“…The Random Forest method was used as implemented in Trainable Weka Segmentation 37 to statistically distinguish between these phases, as successfully used in HAADF STEM Tomography 72 . Here, we…”
Section: Machine Learning Haadf Stem Image Quantificationmentioning
confidence: 99%
“…The sample used here is a composite of silica nanoparticle aggregates inside a rubber matrix, the bulk sample being 25 % silica by volume (investigated previously [7] by the authors using the technique demonstrated in this work). Figure 6 shows one slice from the experimental data.…”
Section: Application To Real Datamentioning
confidence: 99%
“…A 150-nm diameter, 2-μm long pillar of rubber-silica composite [7] was fabricated using a focussed ion beam instrument and then imaged using an FEI Tecnai F20 at 200 kV under HAADF-STEM conditions (collection angle = 23.7-118 mrad). Images were taken from −76°t o +70°at 2°increments, resulting in a missing wedge of 34°.…”
Section: Experimental Datamentioning
confidence: 99%
See 1 more Smart Citation